Performance of integrated vertical-flow constructed wetland-microbial fuel cells during long-term operation: The contribution of substrate type and vegetation. Issue 3 (June 2022) - Zhong, Fei; Cao, Yi; Pang, Chen; Yu, Chunmei; Chen, Yanhong; Liu, Guoyuan; Lian, Bolin; Wei, Hui; Zhang, Jian; Wu, Juan; Cheng, Shuiping
Abstract: An integrated vertical-flow constructed wetland-microbial fuel cell (CW-MFC) system, consisting of an upflow chamber and a downflow chamber, was designed to treat synthetic sewage wastewater. The potential influence of vegetation (with and without the planting of Canna indica ) and substrate type (ceramsite, quartz and zeolite granules filled in CM-A, CM-B and CM-C, respectively) on the performance of wastewater treatment and electricity generation in the CW-MFCs was evaluated during long-term operation. A two-way analysis of variance (ANOVA) indicated that both vegetation and substrate type significantly affected the effluent ammonium (NH4 + -N) and orthophosphate (PO4 3- -P) concentrations ( p  < 0.05), and the interaction term (i.e., vegetation × substrate type) was significant for both NH4 + -N and PO4 3- -P removal ( p  < 0.05). The efficient N removal in the planted CM-A and CM-C could be partly attributed to the enhanced cathodic denitrification in association with the high-power outputs. After plant removal, the deterioration of wastewater treatment and electricity generation performance was observed in all of the CW-MFCs except for CM-A. Using ceramsite as the substrate of a CW-MFC would contribute to a promising performance. However, the increased nirK / nirS and nosZ /16 S rDNA ratios indicated a risk of N2 O emission in the unplanted CM-A, while the gradual decrease in the PO4 3- -P removal efficiency indicated the saturation of adsorption sites on the ceramsite granules after two years of operation. Graphical Abstract: ga1 Highlights: Ceramsite and zeolite could be ideal substrates for planted IVCW-MFCs. Performance of ceramsite filled IVCW-MFC was the best with and without vegetation. NH4 + -N removal efficiency in zeolite filled IVCW-MFC without plant was compromised. NH4 + -N removal in anode and cathode regions occurred in ceramsite filled IVCW-MFC. Efficient N removal was associated with high-power outputs.